Owners, External Managers, and Industrial Relations in German Establishments - Arnd Kölling; Claus Schnabel (Institute of Labor Economics (IZA), 2019)
Using data from the representative IAB Establishment Panel in Germany and estimating a panel probit model with fixed effects, this paper finds a negative relationship between the existence of owner-management in an establishment and the probabilities of having a works council or a collective bargaining agreement. We show that family firms which are solely, partially or not managed by the owners significantly differ in the presence of works councils and collective bargaining agreements. The probabilities of having works councils and collective agreements increase substantially if just some of the managers do not belong to the owner family. We argue that these differences cannot simply be attributed to an aversion of the owners against co-determination and unions but require taking account of the notion of socio-emotional wealth prevalent in family firms. In addition, our results support the idea that external managers mainly act as agents rather than stewards in family firms.
Keywords: J53; M54; G32; 330; industrial relations; co-determination; works council; collective agreement; family firm; Germany